2005
DOI: 10.1345/aph.1e099
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled Tobramycin in Non—Cystic Fibrosis Patients with Bronchiectasis and Chronic Bronchial Infection with Pseudomonas Aeruginosa

Abstract: Aerosol administration of high-dose tobramycin in non-CF bronchiectatic patients for endobronchial infection with PA appears to be safe and decreases the risk of hospitalization and PA density in sputum. Nevertheless, pulmonary function and quality of life are not improved, and the risk of bronchospasm is appreciable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
159
0
16

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(202 citation statements)
references
References 31 publications
11
159
0
16
Order By: Relevance
“…Several studies with inhaled tobramycin have shown a reduction in Pseudomonas bacterial load. [42][43][44][45][46] In addition, studies reported lower exacerbation or hospitalization rates in subjects receiving inhaled tobramycin. [44][45][46] In a study by Dhar et al, 43 nebulized colomycin appeared to reduce exacerbation frequency, hospitalization, and sputum volume in P. aeruginosa-colonized subjects with NCFB.…”
Section: Non-cystic Fibrosis Bronchiectasismentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies with inhaled tobramycin have shown a reduction in Pseudomonas bacterial load. [42][43][44][45][46] In addition, studies reported lower exacerbation or hospitalization rates in subjects receiving inhaled tobramycin. [44][45][46] In a study by Dhar et al, 43 nebulized colomycin appeared to reduce exacerbation frequency, hospitalization, and sputum volume in P. aeruginosa-colonized subjects with NCFB.…”
Section: Non-cystic Fibrosis Bronchiectasismentioning
confidence: 99%
“…[42][43][44][45][46] In addition, studies reported lower exacerbation or hospitalization rates in subjects receiving inhaled tobramycin. [44][45][46] In a study by Dhar et al, 43 nebulized colomycin appeared to reduce exacerbation frequency, hospitalization, and sputum volume in P. aeruginosa-colonized subjects with NCFB. Murray et al 47 reported an RCT of twice-daily nebulized gentamicin compared with placebo that showed long-term nebulized gentamicin was associated with reduced P. aeruginosa and other bacterial density, less sputum purulence, and greater exercise capacity.…”
Section: Non-cystic Fibrosis Bronchiectasismentioning
confidence: 99%
“…10 Although not thoroughly discussed, SCr measurements remained within normal limits throughout the duration of the study period.…”
Section: Discussionmentioning
confidence: 83%
“…Two studies compared twice daily nebulised tobramycin with placebo, one cyclically (4 weeks treatment, 2 weeks off) and the other daily for six months. 26,27 In both studies there was a reduction in bacterial density in the sputum but a small increased incidence of bronchospasm in the treatment arms. Another study compared nebulised ceftazidime and tobramycin with placebo for 12 months.…”
Section: Long-term Antibioticsmentioning
confidence: 95%